Remnant-Like Particle Cholesterol, Low-Density Lipoprotein Triglycerides, and Incident Cardiovascular Disease - Saeed, Anum; Feofanova, Elena V; Yu, Bing; Sun, Wensheng; Virani, Salim S; Nambi, Vijay; Coresh, Josef; Guild, Cameron S; Boerwinkle, Eric; Ballantyne, Christie M; Hoogeveen, Ron C (Journal of the American College of Cardiology, 2018)
Hypertriglyceridemia is associated with increased remnant-like particle cholesterol (RLP-C) and triglycerides in low-density lipoprotein (LDL-TG). Recent studies have focused on atherogenicity of RLP-C, with few data on LDL-TG. The aim of this study was to examine associations of RLP-C and LDL-TG with incident cardiovascular disease (CVD) events and genetic variants in the ARIC (Atherosclerosis Risk In Communities) study. Fasting plasma RLP-C and LDL-TG levels were measured in 9,334 men and women without prevalent CVD. Participants were followed for incident CVD events (coronary heart disease and ischemic stroke) for up to 16 years. Associations between LDL-TG and RLP-C levels and genetic variants were assessed by whole-exome sequencing using single-variant analysis for common variants and gene-based burden tests for rare variants; both an unbiased and a candidate gene approach were explored. RLP-C and LDL-TG levels were correlated with triglyceride levels (r = 0.85 and r = 0.64, p < 0.0001). In minimally adjusted analyses, RLP-C and LDL-TG were associated with CVD risk, but in models adjusted for traditional risk factors including lipids, only LDL-TG was associated with incident CHD (hazard ratio: 1.28; 95% confidence interval: 1.10 to 1.50) and stroke (hazard ratio: 1.47; 95% confidence interval: 1.13 to 1.92). A common APOE variant, rs7412, had the strongest association with LDL-TG and RLP-C (p < 5 × 10 ). RLP-C and LDL-TG levels were predictive of CVD and associated with APOE variants. LDL-TG may represent a marker of dysfunctional remnant lipoprotein metabolism associated with increased CVD risk. Further research is needed to determine whether LDL-TG plays a causal role in CVD and may be a target for therapy.